Edukasi penggunaan obat antinyeri rasional untuk pekerja TPS di Banjarmasin - Hendera Hendera; Risna Purnama Dewi; Rosidah Rahmah; Sari Ena Syafitri; Siti Sirojur Rizki; Sri Desi Safitri (INDRA: Jurnal Pengabdian kepada Masyarakat, 2026)
Background: The misuse of analgesics among waste workers in South Kalimantan reaches 8.5%, with 80% using pain medication without a prescription. This poses significant health risks, including dependency and organ damage. Objective: To improve knowledge and promote rational analgesic use through structured education. Methods: A quasi-experimental pre-post-test study was conducted on 30 waste workers at the Surgi Mufti landfill, Banjarmasin. Interventions included interactive education, demonstrations, individual counseling, and health screenings. Results: Significant improvements were observed in participants' knowledge: safe dosage understanding increased from 40% to 90%, awareness of side effects rose from 35% to 85%, and recognition of dependency risks improved from 30% to 95%. Irrational drug use decreased by 70%, while consultations with healthcare professionals increased by 85%. Conclusion: Structured education effectively enhances health literacy and promotes rational analgesic use among waste workers. Recommendations include integrating this program into local occupational health policies and developing digital-based educational materials for broader outreach.